이유자돈, 육성돈 및 비육돈에 있어 게르마늄흑운모의 급여 효과 - 권오석; 김인호; 홍종욱; 이상환; 정연권; 민병준; 이원백; 손경승; Kwon, O.S; Kim, I.H; Hong, J.W; Lee, S.H; et al. (Journal of animal science and technology, 2003)
In Exp. 1, this study was conducted to determine the effect of dietary germanium biotite on growth performance and nutrient digestibility in nursery pigs. A total of sixty crossbred pigs (initial body weight 15.09$±$0.18kg) were used in this experiment. This study was carried out for 28 days. The five treatments were control (CON; basal diet), GB0.1 (basal diet + germanium biotite 0.1%), GB0.3 (basal diet + germanium biotite 0.3%), GB0.6 (basal diet + germanium biotite 0.6%) and GB1.0 (basal diet + germanium biotite 1.0%). For overall period, ADG and Gain/feed were not significantly different among the treatments. In Exp. 2, a study was conducted to evaluate the effect of germanium biotite as a substitute for antibiotics in growing pigs. A total of fifty five crossbred pigs (initial body weight 32.47$±$0.9kg) were used in this experiment. The three treatments were negative control (NC: basal diet without antibiotic), positive control (PC: basal diet + 200ppm CTC) and GB0.3 (basal diet + germanium biotite 0.3%). Pigs fed PC (17%, 385 vs 451 g/d) and GB0.3 (14%, 385 vs 438 g/d) diets grew faster(P<0.05) than pigs fed NC diet. Pigs fed PC and GB0.3 diets resulted higher(P<0.05) ADFI than pigs fed CON diet. However, pigs fed GB0.3 diet had improved gain/feed compared to pigs fed NC diet(P<0.05). Apparent digestibility of DM and N by pigs fed PC and GB0.3 diets were greater(P<0.05) than those by pigs fed NC diet. In Exp. 3, a study was conducted to determine the effect of dietary germanium biotite on growth performance, plasma characteristics, backfat thickness and fecal ammonia gas concentration in finishing pigs. A total of seventy-two finishing pigs (initial body weight 78.56$±$1.32kg) were used in this experiment. The treatments included 1) Control (CON; basal diet) 2) GB1.0 (basal diet + germanium biotite 1.0%), 3) GB3.0 (basal diet + germanium biotite 3.0%). Pigs fed GB1.0 diet grew faster than pigs fed CON diet and GB0.3 diet (P<0.05). Also, pigs fed CON diet showed higher(p<0.05) ADFI than pigs fed GB3.0 diet. Pigs fed GB diets had improved gain/feed compared to pigs fed CON diet(P<0.05). Total?and VLDL concentrations in plasma of pigs fed GB diets treatments were significantly decreased compared to those in pig fed CON diet(P<0.05). However, HDL-cholesterol concentration in plasma of the pig was significantly increased compared to those in pigs fed CON diet (P<0.05). Pigs fed CON diet exerted higher(P<0.05) backfat thickness than pigs fed GB1.0 (5.4%, 27.19 vs 25.71mm) and GB3.0 (16.1%, 27.19 vs 22.81mm) diets. Feces from CON treatment were higher in fecal ammonia gas concentration than faces from pigs fed GB1.0 (64.1%, 17.00 vs 6.10mg/kg)and GB3.0 (61.8%, 17.00 vs 6.50mg/kg) treatments(P<0.05). In conclusion, the results suggest that the dietary addition of germanium biotite into diets for nursery pigs did not affect growth performance. The results also suggest the possibility of germanium biotite to replace antibiotic in diets for growing pigs. In finishing pigs, dietary supplementation of germanium biotite was an effective means for improving growth performance and for decreasing Total-and LDL+VLDL-plasma cholesterols, backfat and fecal ammonia gas concentration. 시험 1은 게르마늄흑운모를 자돈 사료에 첨가하였을 때 자돈의 성장 및 영양소 소화율에 미치는 영향을 평가하고자 실시하였다. 공시동물은 평균 체중 15.09$±$0.18kg의 3원 교잡종 자돈 60두를 공시하여 28일간 실시하였다. 시험설계는 기초사료에 게르마늄흑운모 무첨가구 (CON; basal diet), 기초사료에 게르마늄흑운모 0.1%(GB0.1), 0.3%(GB0.3), 0.6%(GB0.6), 1.0% (GB1.0) 첨가구로 5개 처리로 하였다. 전체 사양시험 기간동안, 일당증체량과 사료효율에 있어서는 처리구간에 유의적인 차이를 보이지 않았다. 시험 2는 육성돈 사료내 게르마늄흑운모의 항생제 대체효과를 평가하기 위하여 실시하였다. 공시동물은 평균 체중이 32.47$±$0.90kg인 3원 교잡종 육성돈 54두를 공시하여 35일간 실시하였다. 시험설계는 기초사료에 항생제 무첨가구(NC; basal diet), 항생제 첨가구 (PC; basal diet + 200ppm CTC), 게르마늄흑운모를 0.3% 첨가구(GB0.3; basal diet + 0.3% germanium biotite)의 3개 처리로 하였다. 사양시험 기간동안, 일당증체량에 있어서 NC 처리구와 비교하였을 때 PC 처리구와 GB0.3 처리구의 성장율이 각각 17%(385 vs 451, g/d), 14% (385 vs 438, g/d) 높았다(P<0.05). 일당사료섭취량에 있어서 NC 처리구와 비교하여 PC 처리구와 GB0.3 처리구가 유의적으로 높았다(P<0.05). 사료효율에 있어서도 NC 처리구와 비교하여 GB0.3 처리구가 유의적으로 높았다(0.323 vs 0.332)(P<0.05). 외관상 건물과 질소 소화율에 있어서 NC 처리구와 비교하여 PC 처리구와 GB0.3 처리구가 유의적으로 높았다 (P<0.05). 시험 3은 비육돈 사료내 게르마늄흑운모의 첨가가 성장, 영양소 소화율, 혈장 성상, 등지방 두께 그리고 분내 암모니아 가스 농도에 미치는 영향을 평가하기 위하여 실시하였다. 공시동물은 평균 체중이 78.65$±$1.32kg인 비육돈 72두를 공시하였다. 시험설계는 기초사료에 게르마늄흑운모 무첨가구 (CON; basal diet), 기초사료에 게르마늄흑운모 1.0% (GB1.0), 3.0% (GB 3.0) 첨가구로 3개 처리로 하였다. 사양시험 기간동안, 일당증체량에서는 GB1.0 처리구가 대조구와 GB3.0 처리구와 비교하여 유의적으로 높았으며 (P<0.05), 일당사료섭취량에 있어서는 대조구가 GB3.0보다 유의적으로 높았다 (P< 0.05). 사료효율에 있어서는 GB 첨가구가 대조구와 비교하여 유의적으로 높게 조사되었다 (P<0.05). 혈장내 Total-cholesterol 함량 변화는 대조구와 비교하여 게르마늄흑운모 첨가구가 유의적으로 감소하였다(P<0.05). 또한, LDL+ VLDL-cholesterol 함량 변화도 대조구와 비교하여 게르마늄흑운모 첨가구가 유의적으로 감소하였다(P<0.05). 혈장내 HDL-cholesterol 함량에 있어서는 대조구와 비교하여 게르마늄흑운모 첨가구가 유의적으로 증가하였다(P<0.05). 등지방 두께에 있어서는 대조구와 비교하여 GB1.0 처리구가 5.4% (27.19 vs 25.71mm)의 감소를 보였고, GB3.0 처리구가 대조구와 비교하여 16.1% (27.19 vs 22.81mm)로 유의적인 감소하였다 (P<0.05). 게르마늄흑운모의 분내 암모니아 가스 농도에 미치는 영향에 있어서는, 대조구와 비교하여 GB1.0 처리구가 64.1% (17.00 vs 6.10mg/kg), GB3.0 처리구가 61.8% (17.00 vs 6.50mg/kg) 유의적으로 감소하였다 (P<0.05). 결론적으로, 양돈사료내 게르마늄흑운모를 첨가하였을 경우, 자돈에 있어서는 성장에 영향을 미치지 않는 것으로 사료되며, 육성돈에 있어서는 항생제 대체효과를 갖는 것으로 나타난다. 또한, 비육돈 사료내 게르마늄흑운모의 첨가는 비육돈의 성장능력을 향상시키는 것으로 판단되며,